Back Picture: Plasma Process. Polym. 4–5∕2017. Issue 4 (25th April 2017) - Georgieva, Violeta; Berthelot, Antonin; Silva, Tiago; Kolev, Stanimir; Graef, Wouter; Britun, Nikolay; Chen, Guoxing; van der Mullen, Joost; Godfroid, Thomas; Mihailova, Diana; van Dijk, Jan; Snyders, Rony; et al.
Abstract : Back Cover: Cross‐sectional view of a microwave plasma column at a pressure of 933 Pa. The Ar, N2 or CO2 plasma is sustained by a surfaguide launcher. Modeling shows that the power is deposited along the plasma‐dielectric boundary (the tube wall), where the surface wave propagates. This paper presents and benchmarks two 2‐dimensional models (quasi‐neutral and plasma bulk‐sheath, both accounting for the gas flow) for Ar microwave plasma and compares the results with the experiment. Further details can be found in the article by V. Georgieva et al. at1600185 .